American legal realism: towards a new approach to the privatization of Omar Effendi in Egypt - Mikhael, Peter Maurice (AUC Knowledge Fountain, 2015)
This paper presents to its readers the progressive legal evolution that has influenced, over the past century, legal reform in American history. It focuses specifically on American legal realist thinking that was considered revolutionary in nature relative to the natural and formalist schools of jurisprudence. The focus then shifts to Egypt where the combination of formal and natural jurisprudence is clear to legal scholars. Omar Effendi, as one of the most prominent case decision in the post-25th January revolution period, was both criticized and lauded for political reasons. Scholars that supported the decision were glad that the corrupt privatization of a well-known company ended with the State Council's decision. Opponents feared that the state courts’ interference in the commercial contractual relationship would negatively affect investment prospects in Egypt. This paper analyzes the application of law in a changing political context and concludes with the proof that legal realists strived to achieve: the implementation and execution of law are pure acts of political choice.